2007
DOI: 10.1504/ijeh.2007.013103
|View full text |Cite
|
Sign up to set email alerts
|

Hospital information management system: an evolutionary knowledge management perspective

Abstract: The evolving paradigm shift resulting from IT, social and technological changes has created a need for developing an innovative knowledge-based healthcare system, which can effectively meet global healthcare system demands and also cater to future trends. The Hospital Information Management System (HIMS) is developed with this sole aim in mind, which helps in processing and management of hospital information not only inside the boundary, but also beyond the hospital boundary, e.g., telemedicine or e-healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…Bai and Srivatsa (2007) discuss the design of a wearable cardiac telemedicine system that can help the mobility of patients, so as to regain their independence and return to an active social or work schedule, thereby improving their psychological well-being. Wadhwa et al (2007) propose a functional Hospital Information Management System (HIMS) which helps in processing and management of internal and inter-organisational hospital information, e.g., telemedicine or e-healthcare. The proposed system is fully compatible with future technical, social, managerial and economical requirements.…”
Section: Future Trendsmentioning
confidence: 99%
“…Bai and Srivatsa (2007) discuss the design of a wearable cardiac telemedicine system that can help the mobility of patients, so as to regain their independence and return to an active social or work schedule, thereby improving their psychological well-being. Wadhwa et al (2007) propose a functional Hospital Information Management System (HIMS) which helps in processing and management of internal and inter-organisational hospital information, e.g., telemedicine or e-healthcare. The proposed system is fully compatible with future technical, social, managerial and economical requirements.…”
Section: Future Trendsmentioning
confidence: 99%
“…If an independent management department is not currently established, it is suggested that the medical manager, who is responsible for the main management, take on the management role and assume the corresponding responsibilities. Meanwhile, it is recommended that a service management system for internet hospitals be established, considering three aspects: quality and safety, process standardization, and information security [ 19 ]. Of these, patient safety and the risk of treatment errors are particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Wadhwa (2007) proposed a viable vision for healthcare based on the study conducted in the oral and maxillofacial surgery department in which TOC was combined with lean and six sigma. Ferguson and Gelder (2010) presented a Generic Strategy and Tactics tree for the healthcare environment to improve the hospital’s financial performance and provided strategy, parallel assumptions, tactics, necessary assumptions and sufficiency assumptions for the viable vision of hospitals.…”
Section: Tocico Healthcare Studiesmentioning
confidence: 99%